Mongolia : Livestock Sector Study - World Bank (Washington, DC, 2013)
The purpose of this synthesis report is to try and draw together recent work on the sector to understand in greater detail what is driving the sector, and how these drivers and trends may play out in the future and what options are available in response. This is not a strategy for the sector, but rather an attempt to provide some clarity to the development of the sector as a basis for stimulating discussion to inform strategy and specifically, to inform government policy and expenditure in the sector. The report draws upon five working papers (WPs) that were commissioned by the Ministry of Food and Agriculture in 2006 and 2007 . These papers tried to fill gaps in current knowledge of drivers in the sector rather than provide a comprehensive study of the sector, and their findings have been supplemented by other work in the sector.